Intraoperative endoscopic treatment of Mirizzi syndrome in a pediatric patient - Nicole A. Wilson; Derek Wakeman; Elizabeth C. Utterson; Adam M. Vogel (Elsevier, 2016)
Mirizzi syndrome occurs when an impacted gallstone, together with an associated inflammatory response, causes external obstruction of the common hepatic duct or common bile duct. Patients classically present with obstructive jaundice, right upper quadrant pain, and sometimes with fever. Mirizzi syndrome is a rare presentation of complicated gallstone disease and is even more rare in the pediatric population. However, as the number of obese pediatric patients increases, so does the incidence of gallstone-related disease. We present a case of Mirizzi syndrome treated by open cholecystectomy and cystic duct stone extraction in a pediatric patient. Recognition and awareness of Mirizzi syndrome is important, even in the pediatric population, to aid in safe operative intervention and to avoid intraoperative bile duct injury.